Bibliometric Analysis of Personality Traits and Behavioral Biases in Financial Decision Making: Mapping the Psychological Landscape of Investment Behavior: Analisis Bibliometrik atas Sifat Kepribadian dan Bias Perilaku dalam Pengambilan Keputusan Keuangan: Memetakan Lanskap Psikologis Perilaku Investasi - Arief Budiman; Raden Dian Hardiana (Jurnal Akuntansi, Keuangan dan Perpajakan, 2026)
This study maps research on how Big Five personality traits relate to behavioral biases in investment decision-making through a bibliometric analysis. It reviews 1,009 publications from 2005 to 2025 and synthesizes patterns in keywords and themes with VOSviewer and Biblioshiny. The findings suggest that decision-making, investment behavior, and risk perception consistently anchor the field, whereas mental health, financial literacy, and cultural context are gaining visibility but remain only loosely connected to the main theoretical stream. The results can inform personality-informed financial education and advisory practices and encourage future work that is culturally grounded and longitudinal. ABSTRAKStudi ini memetakan riset mengenai hubungan Big Five personality traits dengan bias perilaku dalam pengambilan keputusan investasi melalui analisis bibliometrik. Sebanyak 1.009 publikasi periode 2005–2025 ditelaah untuk merangkum pola kata kunci dan perkembangan tema, dengan bantuan VOSviewer dan Biblioshiny. Hasil analisis menunjukkan bahwa pengambilan keputusan, perilaku investasi, dan persepsi risiko secara konsisten menjadi tema inti yang membentuk struktur literatur. Sementara itu, isu kesehatan mental, literasi keuangan, dan konteks budaya semakin banyak dibahas, namun masih berjejaring lemah dengan arus teori utama. Temuan ini mendukung perancangan edukasi dan advis investasi yang lebih adaptif serta peka konteks.